Analisa Vegetasi Jenis Pohon pada Kawasan Hutan di Kampung Tablanusu Distrik Depapre Kabupaten Jayapura - Rosye H.R. Tanjung; Supeni Sufaati; Lucia Runggeari (Jurnal Biologi Papua, 2010)
Tropical rain forest of Papua is very diverse in its floristic composition. Increasing human population cause the loss of forest for farming, urban areas or other human activities which cause deforestation.  The objective of this study was to obtain  the description of composition and structure as well as ecological value of  forest area at Tablanusu Village, District of Depapre. Study was carried out from January – June 2009. Quadrat plot (50 m x 20 m) were placed at  30 m a.s. l and 200 m a.s.l. . Index of Shannon-Wieners was used to determine the level of species diversity and Index of Similarity to indicate degree  of similarity of composition between two different altitudes. Results of the study revealed that  at 30 m a.s.l occupied by   25 species  that grouped into 18 families of trees  (ø > 10 cm)  with total 146 trees., sapling (ø 2-10 cm) was  consisted of 26 species  of 15 families  and 74  individuals. While  at 200 m asl, there were 18 species of tress   (ø > 10 cm) which grouped into 13 families with 93 individuals, 23  species of sapling (ø 2-10 cm)  that grouped into 20 families with total  number of individu was 82. The value of Similarity indices of the  tree at 30 m asl and 200 m asl  was 0%, on the other hand for sapling its value showed 12,24 %. It means  that there was a differences in  the species composition on both areas. Furthermore, the  species wich has highest Important value at 30 m asl was  Cocos nucifera L. (63,84 %) for trees and Kleinhovia hospita L. (37,61 %) for sapling.  While  at 200 m asl, this highest value for trees was  found in Instia bijuga OK. (81,67 %), and Mastixiodendron pachyclados K.Sch (41,31 %) for sapling. Eventhough the regeneration procees in those forest was slow, but it has high ecological value, for example as water suply, preventing erotion, habitat of fauna and maintaining the microclimate.   Keywords : analysis of forest vegetation, tree species, Tablanusu  village, Depapre.